Differences in MyoD, YAP, and TAZ mRNA expression in Skeletal Muscle of Wistar Rats Induced by Single-Bout and 8-Week Resistance Training - Dhaifina Fajri Amasyitha; Nova Sylviana; Setiawan (UPT Publikasi Ilmiah Universitas Islam Bandung, 2025)
Sedentary lifestyles contribute to reduced physical fitness and muscle mass. Resistance training (RT) promotes skeletal muscle hypertrophy through mechanical, metabolic, and hormonal stimuli, regulated by satellite cells and myogenic regulatory factors (MRFs), such as MyoD. Yes-associated protein (YAP) and transcriptional coactivator with PDZ-binding motif (TAZ), downstream effectors of the Hippo pathway, are also implicated in muscle regeneration and growth, though their precise mechanisms remain unclear. This study investigated the expression of MyoD, YAP, and TAZ mRNA in rat gastrocnemius muscle following a single bout of resistance training and 8 weeks of resistance training. Fifteen male Wistar rats were randomly assigned to control (CON), single-bout resistance training (SBRT), and 8-week resistance training (8WRT) groups (n=5/group). We conducted resistance training with 15 male Wistar rats using a vertical ladder-climbing protocol and progressive loads in the Science Laboratory Postgraduate Building at Padjajaran University, Dipati Ukur, and in the Central Laboratory at Padjajaran University, Jatinangor, from September 2024 to January 2025. Gastrocnemius muscle samples were collected, and mRNA expression of MyoD, YAP, and TAZ was analyzed via qPCR. Statistical analysis used appropriate parametric or non-parametric tests depending on data distribution. YAP and TAZ expression were significantly increased in SBRT and 8WRT compared to CON (p<0.05), with SBRT showing the highest YAP and 8WRT the highest TAZ levels. MyoD expression decreased significantly in both trained groups (p=0.011), with a non-significant increase in 8WRT compared with SBRT. In conclusion, both SBRT and 8WRT significantly alter MyoD, YAP, and TAZ mRNA expression, suggesting activation and differentiation of satellite cells in response to RT, indicating its involvement in acute and chronic adaptation.